Research on general design of light tour maglev train - GENG Qinghou; ZONG Lingxiao; YANG Jun; MA Weihua; ZHANG Shuo (机车电传动)
By analyzing and comparing the application scenarios and service targets of the large-capacity and medium-capacity maglev trains and light tour maglev trains, the top-level design indicators of the light tour maglev trains was defined based on the elements such as functions, safety, environment and economy, and studied the general design and the main system design of the train. Based on the requirements of train traction and levitation capacity, the overall framework of the running mechanism was designed and developed a scheme of a single car being equipped with two levitation frames, reducing the unsprung weight of the train and the difficulty of equipment maintenance and increasing the space for the equipment under the car. To achieve the goal of "reaching peak carbon emissions and carbon neutrality", a plan to supply power for the light tour maglev train by train-mounted batteries was proposed, which avoided the current receiving of power supply rail and reduced the cost of line construction. The design scheme of each subsystem of the train by theory and simulation was verified, proving the feasibility of the general design of the train. The scheme of the light tour maglev train is innovative, economical, feasible and practical, which can provide inspirations and methods for the design of various types of maglev trains.